Answer:
[tex]d=6\sqrt{2}[/tex]
or
[tex]d = 8.48[/tex]
Step-by-step explanation:
Given:
The given points are (3,-4) and (-3,2).
Assume, we need to find the distance between two points.
Solution:
Distance formula of the two points.
[tex]d = \sqrt{(x_{1}-x_{2})^{2}+(y_{1}-y_{2})^{2} }[/tex]
Now we substitute give points (3,-4) and (-3,2) in above equitation.
[tex]d=\sqrt{(-3-3)^{2}+(2-(-4))^{2}}[/tex]
[tex]d=\sqrt{(-6)^{2}+(2+4)^{2}}[/tex]
[tex]d=\sqrt{36+(6)^{2}}[/tex]
[tex]d=\sqrt{36+36}[/tex]
[tex]d=\sqrt{72}[/tex]
[tex]d=6\sqrt{2}[/tex]
or
[tex]d = 8.48[/tex]
Therefor, the distance between the given points [tex]d=6\sqrt{2}[/tex] or [tex]d = 8.48[/tex]